When does corporate venture capital add value for new ventures? - Park, Haemin Dennis; Steensma, H. Kevin (Strategic Management Journal, 2012)
New ventures face a trade‐off when considering corporate venture capital (CVC) funding. Corporate investors can provide complementary assets that enhance the commercialization of new venture technologies. However, tight links with a particular corporate investor has drawbacks and may constrain new ventures from accessing complementary assets from diverse sources in an open market. Taking this trade‐off into account, we explore conditions under which CVC funding is beneficial to new ventures. Using a sample of computer, semiconductor, and wireless ventures, we find that CVC funding is particularly beneficial for new ventures when they require specialized complementary assets or operate in uncertain environments. Copyright © 2011 John Wiley & Sons, Ltd.